Detecting Runoff Variation of the Mainstream in Weihe River - Qiang Huang; Jingjing Fan (Journal of Applied Mathematics)
The runoff change in Weihe River is significantly decreasing with the climate change and the huge increasing of human activities. The analysis of the variation changes of runoff would provide scientific understanding of Weihe River basin and similar basins. Mann-Kendall method is used to detect the variation changes of annual and seasonal runoff of 1919–2011 at the outlet station, that is, Huaxian station, in the mainstream of Weihe River. The results show that the runoff variation point is 1990, and there were significant changes in trends and periodicals, corroborated by wavelet variance analysis, Kendall’s rank tests, and trends persistence test, in annual, seasonal, and monthly runoff at the variation point of 1990. Attribution analysis indicates that the primary drivers of the shift in runoff variation were human activities rather than climate change, as water consumption (particularly groundwater consumption) increased sharply in the 1990s.